Manajemen Nutrisi pada Pasien ICU yang Menjalani Prosedur Esofagektomi - Widodo, Untung; Jufan, Akhmad Yun; Adrin, Olga Elenska (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2022)
Patients in intensive care are generally exposed to catabolic stress with complications that increase morbidity and mortality, and affect the length of stay in the intensive care unit. Optimal nutritional management can help enhance the metabolic response to stress, prevent oxidative cellular injury, and modulate the immune response. We reported a 30 years old male underwent an esophagectomy procedure due to esophageal tumor. After the third day of surgery the patient was given enteral nutrition, there was a brownish residue in the nasogastric tube, in exchange of this condition, parenteral nutrition was given until the tenth day of intensive care. Enteral nutrition was continued on the tenth day of care until the patient transferred to the ward on the thirteenth day in the intensive care unit.